The buzz phase of resource extraction: Liquefied natural gas in Kitimat, British Columbia. Issue 3 (September 2021) - Sax, Marieka; Tubb, Daniel
Highlights: The buzz phase refers to a distinct temporal period in resource extraction. Major projects generate social impacts in the years leading up to operations. These impacts occur whether or not a project becomes operational. Empirical studies of specific projects and places are required. Six provisional themes for research are proposed. Abstract: This article names a distinct temporal period in resource development and extraction—the buzz phase. The buzz phase draws attention to the years (sometimes decades) of speculation, exploration, assessment, and preparation for a major project, including everything that leads up to operations, whether or not a project actually becomes operational. The social impacts of the buzz phase are experienced by people living and working in zones of present and potential resource extraction, transportation, and processing. A workshop on liquefied natural gas (LNG) development carried out in Kitimat, British Columbia (Canada), is discussed to illustrate and outline the social impacts of the buzz phase. Six provisional themes are proposed as possible areas for future research: hope and fatigue; material and social changes; distribution of impacts; affective impacts; imagined futures; and what is left unsaid.